Factors Influencing Customer Satisfaction in Loan Services for Large-Scale Clients in the Western Region - Haranee , Jeerawan; Jantarat , Jaratchwahn (Journal for Developing the Social and Community, 2025)
Background and Aims: This independent study aims to examine the factors of perceived value and service quality that influence customer satisfaction in using loan services for large-scale clients of the Bank for Agriculture and Agricultural Cooperatives (BAAC) in the western region of Thailand, covering eight provinces. The research employed a quantitative methodology using a sample of 400 respondents through an online questionnaire, which demonstrated reliability coefficients ranging from 0.895 to 0.985. Methodology: Data were analyzed using descriptive statistics and multiple regression analysis. The majority of respondents were female customers residing in Kanchanaburi province, married, holding a bachelor's degree, working as farmers, and earning an average monthly income not exceeding 70,000 baht. Results: Inferential statistical analysis revealed that perceived value factors including functional, social, emotional, and price dimensions as well as service quality factors namely reliability, assurance, empathy, and responsiveness significantly influenced customer satisfaction. However, the tangible aspect of service quality did not show a statistically significant effect. Overall, customer satisfaction was rated at a high level (mean score of 4.45), and the model explained 64.2% of the variance in satisfaction (R² = 0.642). Conclusion: Variables influencing customer satisfaction with large-scale lending services in the Western region include perceived value in terms of functionality, social, emotional, price, and service quality in terms of reliability, confidence building, customer awareness, and customer response. This information can be used as a key guideline for planning, improving, and developing the bank's marketing strategies to effectively align with customer needs.